2021
DOI: 10.3389/fphar.2021.710358
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Preserves the Integrity of Blood-Brain Barrier Associated With Upregulation of MCPIP1 in a Murine Model of Focal Ischemic Stroke

Abstract: Tetramethylpyrazine (TMP), a prominent ingredient of Chinese herb Ligusticum chuanxiong Hort, is known to suppress neuroinflammation and protect blood-brain barrier (BBB) integrity. We investigated whether monocyte chemotactic protein-induced protein 1 (MCPIP1, also known as Regnase-1), a newly identified zinc-finger protein, plays a role in TMP-mediated anti-inflammation and neuroprotection. Male C57BL/6 mice were subjected to focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO) for 2 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…To gain a better understanding of BBB disruption and leakage, various tracers are currently used. One of the most popular tracers for assessing the permeability of the BBB is fluorescein isothiocyanate (FITC) labeled dextran [ 67 , 82 , 83 ]. Due to the fluorescein moiety that can be measured even in low concentrations, FITC-dextran serves as a sensitive and reliable marker to determine BBB permeability [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To gain a better understanding of BBB disruption and leakage, various tracers are currently used. One of the most popular tracers for assessing the permeability of the BBB is fluorescein isothiocyanate (FITC) labeled dextran [ 67 , 82 , 83 ]. Due to the fluorescein moiety that can be measured even in low concentrations, FITC-dextran serves as a sensitive and reliable marker to determine BBB permeability [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug dose in the TMP group was 25 mg kg À1 (Harbin Sanlian Pharmaceutical Co., Ltd), as determined by the dose conversion factor for humans and rats and literature reports. 31 The rats in the sham, SCI, GMP, and GMPT groups were injected with an equal volume of saline. All SD rats were injected intraperitoneally once daily for 7 days with the above designed formulations as TMP or saline.…”
Section: 3mentioning
confidence: 99%
“…The monocyte chemotactic protein-induced protein 1 (MCPIP1) is a suppressor of inflammation ( Liang et al, 2010 ). Results from the cerebral I/R mice model induced by MCAO indicated that the TMP treatment effectively upregulates the expression of MCPIP1 and decreases the levels of inflammatory cytokines TNF-α, IL-1β, and IL-6 ( Jin et al, 2021 ). Nuclear factor E2 correlation factor 2 (Nrf2) can regulate the oxidative stress and inflammation response by promoting the expression of the downstream heme oxygenase-1 (HO-1) gene ( He et al, 2020 ).…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%
“…Matrix metalloproteinases-9 (MMP-9) is an enzyme responsible for degrading the extracellular matrix and tight junctions ( Candelario-Jalil et al, 2011 ). TMP treatment was also shown to preserve the BBB integrity by decreasing the levels of MMP-9 ( Tan et al, 2015b ; Jin et al, 2021 ).…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%